Cancer has overtaken cardiovascular disease as the commonest cause of death in Scottish type 2 diabetes patients: A population‐based study (The Ayrshire Diabetes Follow‐up Cohort study). Issue 1 (25th July 2019) - Collier, Andrew; Meney, Carron; Hair, Mario; Cameron, Lyall; Boyle, James G
Abstract: Aims/Introduction: The increased mortality risk associated with diabetes is well established. The aim of the present study was to determine the causes of death of people with type 2 diabetes in Ayrshire and Arran, Scotland, between 2009 and 2014, and compare them with the national mortality rates. Materials and Methods: The primary causes of death were collated. The causes of death were clustered into nine categories: heart disease, stroke, infection, renal failure, respiratory disorders, cancer, mental health, decompensated diabetes and other. The total rates were compared with national rates using the standardized mortality ratio (SMR), and then individually with heart disease, cerebrovascular disease and cancer. Results: There were 2116 deaths with the SMR, and 145 of those were caused by type 2 diabetes ( n = 16, 643; 95% confidence interval 139–152; P < 0.01). The SMR was >100 in all age bands, particularly in the younger age bands ( P < 0.01). The SMR was consistently higher for women ( P < 0.01). The SMR for heart disease was significantly >100 for both sexes in all age bands <65 years ( P < 0.05). There was no difference in mortality causes related to the duration of diabetes. The most common cause of death was cancer (27.8%), followed by heart disease (24.1%). The SMR for cancer deaths was significantly elevated in women (120, 95% CI 104–137; P < 0.05). Conclusions: This study confirmed increased mortality risk in type 2 diabetes patients, and suggests that where cardiovascular risk factors are being treated aggressively, cancer takes on a greater importance in the cause of death. Should greater consideration now be given for cancer as a complication of diabetes?